2022
DOI: 10.1177/09544054221076241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of friction stir spot welding of polymer-aluminum alloy weldments

Abstract: The friction stir spot welding (FSSW) process is one of the main solid-state joining methods used widely for welding different materials and dissimilar metals. In this article, the welding of Polytetrafluoroethylene (PTFE) and aluminum alloy sheets by the FSSW process will be investigated experimentally. The joining of polymer (PTFE) and metal (AA1050 aluminum alloy) was done successfully. The effect of process parameters including tool rotational speed, penetration depth, initial holding time, dwell time, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Pereira et al [50] and Ramesh Rudrapati [51] reported in their reviews that further investigations and research are required to find the appropriate plunge force, temperature, fiber fragmentation degree, tilt angle, tool geometry, and rotational speed for conducting FSW on polymer composites. Jalal Joudaki et al [52] successfully demonstrated the FSW of polymer-AA 1050 (PTFE-Al) composites. Innovations in the current method for fabricating composite FSSW joints provides an ideal framework for fabricating reinforced polymer/polymer matrix composite spot joints to reduce costs and improve productivity, with low environmental impacts, in the aerospace, automobile, and electronic device industries.…”
Section: Wear Behaviormentioning
confidence: 99%
See 3 more Smart Citations
“…Pereira et al [50] and Ramesh Rudrapati [51] reported in their reviews that further investigations and research are required to find the appropriate plunge force, temperature, fiber fragmentation degree, tilt angle, tool geometry, and rotational speed for conducting FSW on polymer composites. Jalal Joudaki et al [52] successfully demonstrated the FSW of polymer-AA 1050 (PTFE-Al) composites. Innovations in the current method for fabricating composite FSSW joints provides an ideal framework for fabricating reinforced polymer/polymer matrix composite spot joints to reduce costs and improve productivity, with low environmental impacts, in the aerospace, automobile, and electronic device industries.…”
Section: Wear Behaviormentioning
confidence: 99%
“…Pereira et al [50] and Ramesh Rudrapati [51] reported in their reviews that further investigations and research are required to find the appropriate plunge force, temperature, fiber fragmentation degree, tilt angle, tool geometry, and rotational speed for conducting FSW on polymer composites. Jalal Joudaki et al [52] successfully demonstrated the FSW of polymer-AA 1050 (PTFE- With the understanding that nano-SiC-reinforced AA5083-H116 joints have higher weld strength than AA5083-H116-only joints, this research methodology can be extended to other materials. In recent years, there has been increased research interest in fabricating polymer joints through the FSW/FSSW processes [50][51][52].…”
Section: Wear Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…FSW expands on the possibilities of dissimilar material combinations by joining workpieces that are difficult or impossible to perform with more traditional methods. Previous FSW research shows joinable dissimilar material pairs, such as metals, 27 polymers, 8 and composites. 9,10 Traditional and derivative FSW processes can weld this wide range of materials.…”
Section: Introductionmentioning
confidence: 99%